2021
DOI: 10.1097/md.0000000000026624
|View full text |Cite
|
Sign up to set email alerts
|

Trefoil factor-2, an early predictor for acute gastrointestinal injury in patients with acute pancreatitis

Abstract: Acute gastrointestinal injury (AGI) is commonly present in patients with acute pancreatitis (AP). It is often difficult to predict gastrointestinal function in the early stage due to lack of reliable markers. We aimed to assess whether early plasma trefoil factor 2 (TFF-2) is a potential predictor for AGI. Fifty one patients were included for the onset of AP (from developing abdominal pain) within 72 hours in this prospective observational single-center study from January 2013 to July 2015. Among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…23 Previous studies showed that angiopoietin-2 and trefoil factor-2 may be the biomarkers of AGI in small sample data. 24,25 Thus, effective predictors of GI injury in the early stages of AP remain lacking.…”
Section: Introductionmentioning
confidence: 99%
“…23 Previous studies showed that angiopoietin-2 and trefoil factor-2 may be the biomarkers of AGI in small sample data. 24,25 Thus, effective predictors of GI injury in the early stages of AP remain lacking.…”
Section: Introductionmentioning
confidence: 99%